Leaders on leadership : wisdom, advice, and encouragement on the art of leading God's people - Barna, George (Ventura, Calif., U.S.A. : Regal Books, 1997)
Presents inspiration and guidance from a variety of leaders, discussing the definition of leadership, new ideas on overcoming the challenges leaders face, and new enthusiasm to answer the call God has placed in your life.
Nothing is more important than leadership / George Barna -- What leaders do / Kenneth O. Gangel -- The vision thing / George Barna -- The character of a leader / Jack W. Hayford -- Becoming a spiritually mature leader / Gene Getz -- Being a tough but tender leader / H.B. London Jr. -- Helping leaders grow / Leighton Ford -- The life cycle of a leader / J. Robert Clinton and Richard W. Clinton -- The role of innovation in leadership / Elmer L. Towns -- The leader as a change agent
Includes bibliographical references.
Keywords: Christian leadership; Leadership -- Religious aspects -- Christianity